If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 2 = 3x + -4 Reorder the terms: 2 + 8x = 3x + -4 Reorder the terms: 2 + 8x = -4 + 3x Solving 2 + 8x = -4 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 2 + 8x + -3x = -4 + 3x + -3x Combine like terms: 8x + -3x = 5x 2 + 5x = -4 + 3x + -3x Combine like terms: 3x + -3x = 0 2 + 5x = -4 + 0 2 + 5x = -4 Add '-2' to each side of the equation. 2 + -2 + 5x = -4 + -2 Combine like terms: 2 + -2 = 0 0 + 5x = -4 + -2 5x = -4 + -2 Combine like terms: -4 + -2 = -6 5x = -6 Divide each side by '5'. x = -1.2 Simplifying x = -1.2
| 25-5v=-2(-3v-6)+2 | | 6+5z=-20 | | 8n-80=704 | | Onethirdy-18=2 | | x+8.2=20 | | 5x=5x+18 | | 10+u=3 | | 5x+1=24x-4 | | -2(6y-3)-y=-2(y-5) | | 2xy=10 | | 6(x-2)=14+4x | | 400+2w=250+5w | | p(6p+7)=0 | | 2x+1-(-2)-(-x)=2-(-2x) | | -2m+23=-7+4(1+6m) | | 23(x-2)=14+4x | | 2xy+6xy-2xy= | | X^2+2x-140=0 | | .75u-6=2.3u+8 | | 14-4x-5=27-10 | | 9x-5x+5=x-4+9 | | 3a-3(a-4)=12+5a | | 6+7x=69 | | 2(7x-1)=-32+8x | | 37-a+25=40 | | 4v^7x^5*3x^2*4v= | | 9x+8(-4x+17)=27 | | 4t-7=3t-1 | | (x^2+5x-528)= | | f(x)=[[-3.4]] | | 8c-4c-20= | | h+441=546 |